2012
DOI: 10.5897/ajmr11.1298
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the contamination level by biogenic amines in fish samples collected from markets in Thuel Saudi Arabia

Abstract: Biogenic amines are formed in some foods, especially fish and fish products as a result of the process of decarboxylation of free amino acids in food. The histamine (scombroid) poisoning arises from ingestion foods containing relatively high levels of histamine and other amines that act as histamine potentiators. Therefore, this study aims to explore the level of contamination by biogenic amines in fish and fish products in shore of Thuel -Saudi Arabia. One hundred and twenty of different fish samples were col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 14 publications
2
1
0
Order By: Relevance
“…The recorded results for histamine concentrations revealed that, the highest histamine contamination was in oyster followed by shrimp followed by Claris lazera then crab then Oreochromis niloticus finally Mugil cephalus. The results for histamine concentrations in fish samples were nearly similar to those obtained by Ekici and Alisarli (2008); Ayesh et al (2012) and Kulawik et al (2016). But they were disagreed with those of Lapa-Guimarães and Pickova 2004; Auerswald et al (2006); Thaw et al (2004); Ayesh et al (2012); Mostafa-Azza and Salem-Rabab (2015); who detected histamine in fish samples with lower concentrations and with those of Tsai et al (2006); Tao et al (2010); Visciano et al (2012) and El-Sayed, Huda (2014) who detected higher levels.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The recorded results for histamine concentrations revealed that, the highest histamine contamination was in oyster followed by shrimp followed by Claris lazera then crab then Oreochromis niloticus finally Mugil cephalus. The results for histamine concentrations in fish samples were nearly similar to those obtained by Ekici and Alisarli (2008); Ayesh et al (2012) and Kulawik et al (2016). But they were disagreed with those of Lapa-Guimarães and Pickova 2004; Auerswald et al (2006); Thaw et al (2004); Ayesh et al (2012); Mostafa-Azza and Salem-Rabab (2015); who detected histamine in fish samples with lower concentrations and with those of Tsai et al (2006); Tao et al (2010); Visciano et al (2012) and El-Sayed, Huda (2014) who detected higher levels.…”
Section: Discussionsupporting
confidence: 89%
“…It united with nitrite to form heterocyclic carcinogenic nitrosamines, nitrosopyrrolidine and nitrosopiperidine. Also, it has a vasoactive activity that may reach to concentrations being dangerous for the most sensitive consumers (Maijala et al 1993).The obtained results for cadaverine concentrations cleared that, the highest cadaverine contamination were in oyster followed by shrimp followed by Claris lazera then Oreochromis niloticus then crab finally Mugil cephalus .The results for cadaverine concentrations in the examined fish samples were nearly similar to those recorded by Lapa- Guimarães and Pickova (2004); Ayesh et al (2012) and Mostafa-Azza and Salem-Rabab (2015). These results were disagreed with those of Thaw et al (2004) and El-Sayed, Huda (2014) who detected cadaverine in fish samples with lower concentrations.…”
Section: Discussionsupporting
confidence: 80%
“…The most well-known role of histamine is mediating part of the inflammatory responses to various allergic reactions [4][5]. Histamine (scombroid) poisoning is associated with the consumption of scombroid fish such as tuna, bonito and mackerel [6]. After fish, cheese is the food in which the highest concentrations -sometimes >1000 mg kg -1 e recorded [7].…”
Section: Introductionmentioning
confidence: 99%